IgE-mediated food allergy - Waserman, Susan (Allergy Asthma Clin Immunol, 2018)
Food allergy is defined as an adverse immunologic response to a food protein. Food-related reactions are associated with a broad range of signs and symptoms that may involve any body system, including the skin, gastrointestinal and respiratory tracts, and cardiovascular system. Immunoglobulin E (IgE)-mediated food allergy is a leading cause of anaphylaxis and, therefore, referral to an allergist for timely and appropriate diagnosis and treatment is imperative. Diagnosis entails a careful history and diagnostic tests, such as skin prick tests, serum-specific IgE and, if indicated, an oral food challenge. Once the diagnosis of food allergy is confirmed, strict elimination of the offending food allergen from the diet is generally necessary; however, in the case of cow’s milk and egg allergy, many allergic children are able to eat these foods in their baked form. This article provides an overview of the epidemiology, pathophysiology, diagnosis, and management of IgE-mediated food allergy.